2021
DOI: 10.3390/molecules26206288
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Power Applications for Protein Conformational Change and the Permeabilization of Agricultural Products

Abstract: Pulsed electric fields (PEFs), which are generated by pulsed power technologies, are being tested for their applicability in food processing through protein conformational change and the poration of cell membranes. In this article, enzyme activity change and the permeabilization of agricultural products using pulsed power technologies are reviewed as novel, nonthermal food processes. Compact pulsed power systems have been developed with repetitive operation and moderate output power for application in food pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 85 publications
(147 reference statements)
0
8
0
Order By: Relevance
“…This is because the PEF exposure on microbial cells would lead to disturbance on the integrity of the cell membrane transiently or permanently (Nowosad et al, 2021). Takaki et al (2021) suggested that the PEF exposure would cause the charging up of the membrane, which further critically affected by the electric field strength and exposure period, leading to irreversible breakdown.…”
Section: Total Plate Countmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because the PEF exposure on microbial cells would lead to disturbance on the integrity of the cell membrane transiently or permanently (Nowosad et al, 2021). Takaki et al (2021) suggested that the PEF exposure would cause the charging up of the membrane, which further critically affected by the electric field strength and exposure period, leading to irreversible breakdown.…”
Section: Total Plate Countmentioning
confidence: 99%
“…In this research, it can be clearly observed that the pre-heating combined with PEF exposure in raw milk results in significant decrease (p < 0.05) of emulsion stability of raw milk (Table 3). This is because the heat treatment leads to conformational changes on the milk proteins, especially in the long period of exposure (Takaki et al, 2021). This might be due to the absorption of energy by polar groups of protein during PEF treatment generating the free radicals.…”
Section: Emulsion Stabilitymentioning
confidence: 99%
“…PEF enables the inactivation of microorganisms and simultaneously protects the desired sensory and physical characteristics of food products. However, PEF induces conformational changes in proteins and thus may affect the activity of native enzymes [ 23 , 24 , 25 ]. The quality of plant-derived products depends on the storage atmosphere [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, high-voltage pulses are placed between two electrodes for a brief time; depending upon the voltage supplied, the PEF is categorized into low/moderate-intensity PEF kV/m) and high-intensity PEF (2000-4500 kV/m) [19]. PEF works on the electrical breakdown and electroporation process (formation of holes in the cell membrane and phospholipid bilayers) [15,20]. PEF treatment can result in an interruption in the plant cell wall that can help in improving the extraction process of target compounds [21].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the applied electric field can modify the electrical sensitive components and accelerate heat and mass transfer in drying and freezing processes [10]. PEF treatment also alters the proteins'/enzymes' structure [20] and the polarization of molecules with dipole moments (changes can be reversible or irreversible depending upon the molecules and treatment conditions) [15]. Additionally, the effectiveness of PEF treatment depends upon the food matrix (pH, composition, electrical conductivity) and operating parameters (electric field intensity, pulse polarity, pulse shape, treatment time, and frequency) [22].…”
Section: Introductionmentioning
confidence: 99%